2015
DOI: 10.1016/j.tiv.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of (±)α-tocopherol on brominated diphenyl ether-47-stimulated prostaglandin pathways in human extravillous trophoblasts in vitro

Abstract: Brominated diphenyl ether (BDE)-47 is a prevalent flame retardant chemical found in human tissues and is linked to adverse pregnancy outcomes in humans. Because dysregulation of the prostaglandin pathway is implicated in adverse pregnancy outcomes, the present study investigates BDE-47 induction of prostaglandin synthesis in a human extravillous trophoblast cell line, HTR-8/SVneo, examining the hypothesis that BDE-47 increases generation of reactive oxygen species (ROS) to stimulate the prostaglandin response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…2014 ), bisphenols ( Kim et al. 2010 ), and brominated flame retardants ( Park and Loch-Caruso 2015 ) have all been shown to impact production in reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…2014 ), bisphenols ( Kim et al. 2010 ), and brominated flame retardants ( Park and Loch-Caruso 2015 ) have all been shown to impact production in reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research suggested that the PBDE toxicity was strongly associated with PBDE-induced oxidative stress and inflammatory reactions. Interestingly, dietary sources of beneficial antioxidants such as flavonoids, α -tocopherol, and omega-3 polyunsaturated fatty acids could protect tissue cells against the toxicity of PBDEs, involved in mitochondrial electron transport system dysfunction, DNA fragmentation, and endoplasmic reticulum stress via blocking the generation of ROS [ 7 , 30 , 31 ]. Troxerutin, a natural flavonoid, possesses the efficacy of antioxidation and anti-inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS leads to the occurrence and development of inflammatory response [ 7 ]. As a result, BDE-47 augments the nuclear translocation of NF- κ B p65 in the liver, promotes the release of IL-6 and IL-8 [ 10 ], and increases the activity of COX-2 in human extravillous trophoblast cell line [ 31 ]. Our results also showed that BDE-47 induced ROS accumulation and TXNIP expression and then activated NLRP3 inflammasome and promoted mature IL-1 β secretion; in turn, triggered the translocation of NF- κ B p65 from the cytoplasm into the nuclear of kidney cells in the mice, advanced the expression of downstream inflammatory factors such as iNOS and COX-2, and ultimately enhanced urine protein production.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing data reveal that BDE-47 induces oxidative stress and in turn mediates DNA damage, mitochondrial dysfunction, and endoplasmic reticulum stress [ 16 , 36 , 37 ]. Recently, antioxidants have been demonstrated to eliminate oxidative stress by scavenging ROS induced by BDE-47 in vitro [ 13 , 14 , 38 ]. Interestingly, we find that troxerutin could effectively reduce oxidative stress-mediated NAD + depletion and ameliorate liver inflammation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies show that natural products α -tocopherol, omega-3 polyunsaturated fatty acids, and troxerutin may be efficient candidate compounds against the damage induced by BDE-47 [ 13 16 ]. Troxerutin is a derivative of naturally occurring bioflavonoid rutin and enriched in fruits, vegetables, tea, coffee, and cereals.…”
Section: Introductionmentioning
confidence: 99%